Natural gas motorcycle - Yaacob, Zulkefli; Abdul Majid, Zulkifli (Universiti Teknologi Malaysia, 1998)
Air pollution generally comes from emission of mobile and non_mobile sources. Pollution from mobile sources, such as vehicle is dominant in city centers throughout Malaysia. Natural gas is acknowledged as being the mainstream alternative fuel. In Malaysia, pollution is not the only reason to introduce natural gas-powered vehicles but economic is another factor. The country has massive, under exploited natural gas reserve. Natural gas reserve is four times larger than oil reserve. As such, a study has been conducted on bi-fuel motorcycles this is the first program in utilizing natural gas for motorcycles in Malaysia. This research is to study the exhaust emission and performance of motorcycles using natural gas and gasoline. A set of conversion kit for NGV motorcycles has been designed and installed or creates a workable motorcycle. A set control system has been design to produce a workable motorcycle before the emission and performance tests been carried out. All Exhaust Emission Test and Chassis Dynamometer Test were conducted at MODENAS, Gurun Kedah with Modenas R&D Department. The performance and emission of a single cylinder fuelled motorcycle with both natural gas and gasoline has been measured. Full load and top gear performance up to 8500 rpm has been covered. The major difference between the two fuels are the exhaust emission from natural gas give a complete combustion which decreases 99.6% of Carbon Monoxide and 72.5% of Unburned Hydrocarbon at a speed of 70km/hr. However, lower calorific value o natural gas and burning velocity, reduces engine power by 15% at high engine speed, without any modification to gasoline engine. These parameters from the study are very important and useful as guidance to the motorcycle industry using natural gas, a leading technology propelling Malaysia for the next millennium with clean city.